Seroprevalence of SARS-CoV-2 across diverse animal species due to viral exposure - Ardalan, Mehrnaz (Kansas State University, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a single-stranded, enveloped RNA virus belonging to the Coronaviridae family, genus Betacoronavirus. Emerging in late 2019, SARS-CoV-2 spread rapidly leading to the global COVID-19 pandemic. Since its emergence, several species of domestic and wild animals have been found susceptible to SARS-CoV-2 infection through experimental inoculation and surveillance activities by detecting a virus in animals. The possibility of zoonotic transmission poses a significant public health concern, particularly in densely populated animal farming operations. The infection of wildlife species raises concerns about the virus's impact on biodiversity and the potential for creating new reservoirs in nature. Therefore, accurate detection of SARS-CoV-2-specific antibodies is crucial for surveillance and epidemiological studies. Cases of SARS-CoV-2 infection have been reported in large cats, hippopotamuses, and gorillas. However, the susceptibility of bison, elk, and other wildlife species to SARS-CoV-2, as well as natural infection in sheep, goats, and cattle, remains poorly understood. Two experiments were conducted to assess the seroprevalence of SARS-CoV-2 antibodies in cattle, sheep, goats, bison, elk, and other wildlife species from several geographically distinct regions in the United States using two commercially available ELISAs targeting the nucleocapsid (N; N-ELISA) and spike (RBD; sVNT) proteins of SARS-CoV-2 and conventional virus neutralization test (VNT). Additionally, we provide an assessment of the performance of these serological detection methods for identifying antibodies against SARS-CoV-2 in these animal species. The first study indicated that 6/691 bovine, 18/707 goats, and 13/698 sheep serum samples were positive for the sVNT, whereas 25/691 bovine, 18/707 goats, and 27/698 sheep serum samples tested positive for the N-ELISA. SARS-CoV-2 positivity rates were slightly higher in goats and sheep compared to bovine using sVNT, while higher seropositivity was observed in bovine and sheep than goat using N-ELISA. However, none of the sVNT-positive cattle, sheep, or goat serum samples showed detectable neutralizing activity against the SARS-CoV-2 using VNT. These results demonstrated a low level of SARS-CoV-2 seroprevalence in cattle, sheep, and goats in the U.S, indicating that these species have low susceptibility to SARS-CoV-2 infection. The second study demonstrated that 7/575 of bison, 4/180 of elk, and 6/147 of the other wildlife species serum samples were seropositive in the sVNT, whereas 24/575 of bison and 6/180 of elk, and 2/147 of the other wildlife species serum samples tested positive by the N-ELISA. Among the sVNT serum samples, 2 samples from bison, 1 sample from elk, and 5 serum samples from other wildlife species (1 cheetah, 1 gorilla, 2 lions, and 1 hippopotamus) had neutralizing antibody titers in the VNT. The presence of neutralizing antibodies in these species indicates their susceptibility to SARS-CoV-2 infection. Overall, our results indicated the necessity of ongoing surveillance of SARS-CoV-2 prevalence in animal species that interact closely with humans, as well as in other wildlife species inhabiting natural environments and zoological settings. This approach enables the assessment of the reservoir potential of diverse animal populations for SARS-CoV-2 and facilitates the implementation of preventive measures to mitigate the risk of virus transmission.
Keywords: SARS-CoV-2; Surveillance; Antibody; Animal species